The impact of PPARα activation on whole genome gene expression in human precision cut liver slices. (December 2015) - Janssen, Aafke; Betzel, Bark; Stoopen, Geert; Berends, Frits; Janssen, Ignace; Peijnenburg, Ad; Kersten, Sander
Abstract Background Studies in mice have shown that PPARα is an important regulator of lipid metabolism in liver and key transcription factor involved in the adaptive response to fasting. However, much less is known about the role of PPARα in human liver. Methods Here we set out to study the function of PPARα in human liver via analysis of whole genome gene regulation in human liver slices treated with the PPARα agonist Wy14643. Results Quantitative PCR indicated that PPARα is well expressed in human liver and human liver slices and that the classical PPARα targets PLIN2, VLDLR, ANGPTL4, CPT1A and PDK4 are robustly induced by PPARα activation. Transcriptomics analysis indicated that 617 genes were upregulated and 665 genes were downregulated by PPARα activation (q value < 0.05). Many genes induced by PPARα activation were involved in lipid metabolism (ACSL5, AGPAT9, FADS1, SLC27A4), xenobiotic metabolism (POR, ABCC2, CYP3A5) or the unfolded protein response, whereas most of the downregulated genes were involved in immune-related pathways. Among the most highly repressed genes upon PPARα activation were several chemokines (e.g. CXCL9-11, CCL8, CX3CL1, CXCL6), interferon γ-induced genes (e.g. IFITM1, IFIT1, IFIT2, IFIT3) and numerous other immune-related genes (e.g. TLR3, NOS2, and LCN2). Comparative analysis of gene regulation by Wy14643 between human liver slices and primary human hepatocytes showed that down-regulation of gene expression by PPARα is much better captured by liver slices as compared to primary hepatocytes. In particular, PPARα activation markedly suppressed immunity/inflammation-related genes in human liver slices but not in primary hepatocytes. Finally, several putative new target genes of PPARα were identified that were commonly induced by PPARα activation in the two human liver model systems, including TSKU, RHOF, CA12 and VSIG10L. Conclusion Our paper demonstrates the suitability and superiority of human liver slices over primary hepatocytes for studying the functional role of PPARα in human liver. Our data underscore the major role of PPARα in regulation of hepatic lipid and xenobiotic metabolism in human liver and reveal a marked immuno-suppressive/anti-inflammatory effect of PPARα in human liver slices that may be therapeutically relevant for non-alcoholic fatty liver disease.